2018
DOI: 10.1186/s12998-018-0181-3
|View full text |Cite
|
Sign up to set email alerts
|

The regional effect of spinal manipulation on the pressure pain threshold in asymptomatic subjects: a systematic literature review

Abstract: BackgroundSpinal manipulation (SM) has been shown to have an effect on pain perception. More knowledge is needed on this phenomenon and it would be relevant to study its effect in asymptomatic subjects.ObjectivesTo compare regional effect of SM on pressure pain threshold (PPT) vs. sham, inactive control, mobilisation, another SM, and some type of physical therapy. In addition, we reported the results for the three different spinal regions.MethodA systematic search of literature was done using PubMed, Embase an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 31 publications
6
28
0
Order By: Relevance
“…Our previous systematic review [9] revealed that the most common methodological problems in this type of literature were the lack of blindness of statistician/ statistical analysis, the failure to report losses and exclusions, and, importantly, the absence of blindness of the subjects. Our study avoided these errors.…”
Section: Methodological Considerations Concerning Our Studymentioning
confidence: 99%
See 3 more Smart Citations
“…Our previous systematic review [9] revealed that the most common methodological problems in this type of literature were the lack of blindness of statistician/ statistical analysis, the failure to report losses and exclusions, and, importantly, the absence of blindness of the subjects. Our study avoided these errors.…”
Section: Methodological Considerations Concerning Our Studymentioning
confidence: 99%
“…In our previous review [9] we theorized that a credible sham procedure should be acceptable both from a psychological point of view (subjects found naïve, and blind) and physiologically (the sham resembling the active intervention). Interestingly, we found in our previous review [9] that when the sham procedure was considered by us to be completely credible, the studies found positive results, with moderate general quality. In retrospect, this criterion may not have been sufficient, as it did not include an actual validation of the sham.…”
Section: Methodological Considerations Concerning Our Studymentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, the effects of spinal manipulative techniques have been explored using biomechanical [5,6] and neurophysiological outcomes, in the latter case studying e.g. neuromuscular response [7][8][9], pain sensitivity [10,11], or autonomic mediated physiology [12][13][14].…”
Section: Introductionmentioning
confidence: 99%